Strategy and Implementation of Technology-Based Student Literacy and Numeracy Improvement - Nirwana, Zahra Fikri Ayu; Utomo, Hari Widi (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2023)
Literacy and numeracy skills and mastery of technology in students for the current era are important to improve. The purpose of this study was to improve students' literacy and numeracy skills through a technology-based approach. This research was conducted in an elementary school, SDN 1 Bogangin Banyumas, involving all students. The method used was descriptive qualitative. The research covered the application of technology in learning, including the use of interactive educational software and online learning platforms, such as the utilization of quizizz, ztype, abcya and other websites. In addition, training for teachers and students in the use of these technologies was also conducted. The results showed that the use of technology in learning significantly improved students' literacy and numeracy skills. Students showed significant improvement in reading comprehension, writing ability and numeracy skills. They also showed higher interest in learning and greater motivation to develop literacy and numeracy skills. In addition, the use of technology also helps students to develop critical, creative and collaborative skills. However, there were some challenges faced during the implementation of the research. These challenges include the inadequate utilization of technology, the training needed for teachers in integrating technology in classroom learning. Based on this, recommendations are given to schools and related parties to continue developing the use of technology in education, including the utilization of available technology facilities, training teachers on technology-based learning for students, and developing a curriculum that integrates technology-based literacy and numeracy.